Effect of replacement of fish meal with processed soybean on growth, digestibility and nutrient retention in Mugil cephalus (Linn.) fry - Kalla, Alok; Garg, S K; Kaushik, C P; Arasu, A R T; Dinodia, G S (Indian Journal of Fisheries, 2011)
Mugil cephalus fry were maintained in glass aquaria filled with inland saline groundwater (15 ppt), and fed on one of the ten (1-10) isonitrogenous diets (energy contents 16.43 kJg-1 to 16.83 k Jg-1) formulated with and without supplementing mineral premix and amino acids (MPA). Fish meal was replaced with equal proportion of hydrothermically processed full fat soybean (Glycine max) at four inclusion levels (25, 50, 75 and 100 g kg-1 of diet). Growth performance was evaluated by feeding the fish once only @ 5% BW d-1 maintained under laboratory conditions (LD 12:12 at 200C) for 70 days. Studies have revealed that growth, per cent gain in body weight, specific growth rate (SGR % d- 1), apparent protein digestibility (APD%), protein effeciency ratio (PER), gross protein retention (GPR) and gross energy retention (GER) increased with increase in the inclusion levels of soybean (upto 75g kg-1 of diet) in comparison with the fish fed on control diet containing fish meal as the protein source. Carcass of such fish also had high contents of protein, fat and energy, while those of moisture and ash contents remained significantly (P<0.05) low. Duncan’s multiple range test have revealed better growth performance in the fry fed on diets (6-10) supplemented with MPA, thus fry fed on diet 9 had significantly (P<0.05) high performance in terms of growth, digestibility and nutrient retention. Ammonia (N-NH+4) excretion and reactive phosphate (o-PO4) production decreased with each increase in the inclusion levels of processed soybean in the diets depicting a negative correlation with growth and digestibility and positive correlation with FCR. These studies thus indicate that fish meal can be replaced by soy protein without compromising weight gain or feed effeciency in the fry of Mugil cephalus.